Teacher's Thoughts regarding the Use of Media in Teaching English - Isnaeni Wahab; Syahira Syahira; Sitti Aisyah; Heriyanti Tahang; Siti Hardianti (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2025)
As the demand for English language proficiency is getting higher nowadays, a teacher as one of the important elements in teaching must maximize and facilitate students in learning. One of the supporting elements in learning is the use of media in helping teachers deliver learning materials. This study aims to determine how English teachers’ thoughts toward the use of media in teaching English. This study was a qualitative study with data collection techniques through observation and interviews. The population in this study was 3 English teachers at Junior High School Kartika XX-I Makassar by using a total sample as a sample selection method. This study used qualitative analysis techniques developed by Miles and Huberman, namely data reduction, data presentation and drawing conclusions. From the results of the data collection carried out that teachers express positive views on the use of media to improve students' English learning abilities. It was known that teachers use LCD, PowerPoint, YouTube, books, and games as media in their learning. Media has an important role in training students to use English. In addition, the use of interesting media can foster students’ motivation and enthusiasm.